Classical dynamics of particles and systems - Marion, Jerry B. (Brooks/Cole, 2004)
This best-selling classical mechanics text, written for the advanced undergraduate one- or two-semester course, provides a complete account of the classical mechanics of particles, systems of particles, and rigid bodies. Vector calculus is used extensively to explore topics.The Lagrangian formulation of mechanics is introduced early to show its powerful problem solving ability.. Modern notation and terminology are used throughout in support of the text's objective: to facilitate students' transition to advanced physics and the mathematical formalism needed for the quantum theory of physics. Classical dynamics of particles and systems, 5th ed., can easily be used for a one- or two-semester course, depending on the instructor's choice of topics.